Re-expansion of vertebral compression fractures in patients with multiple myeloma with percutaneous vertebroplasty using spinejack implants: a preliminary and retrospective study - Pusceddu, Claudio; Faiella, Eliodoro; Derudas, Daniele; Ballicu, Nicola; Melis, Luca; Zedda, Stefano; Marsico, Salvatore (Frontiers in Surgery, 2023)
Objective To retrospectively evaluate the feasibility and effectiveness of vertebroplasty using Spinejack implantation for the treatment and stabilization of painful vertebral compression fractures, in patients diagnosed with Multiple Myeloma (MM), to allow both an effective pain reduction and a global structural spine stabilization. Materials and Methods From July 2017 and May 2022 thirty-nine patients diagnosed MM, with forty-nine vertebral compression fractures underwent percutaneous Vertebroplasty using Spinejack Implants. We analyzed the feasibility and complications of the procedure, the decrease in pain using visual analogue scale (VAS) and Functional Mobility Scale (FMS). Results The technical success rate was 100%. No procedure-related major complications or death occurred. In the 6-month follow-up, the mean VAS score decreased from 5.4 ± 1.0 to 0.2 ± 0.5 with a mean reduction of 96.3%. FMS decreased from 2.3 ± 0.5 vs. 1.2 ± 0.4 with a mean reduction of −47.8%. There were no major complications related to incorrect positioning of the Expandable Titanium SpineJack Implants. In five patients, a cement leak was observed with no associated clinical manifestations. The average length of hospital stay was 6–8 Hours6.6 ± 1.2 h. No new bone fractures or local disease recurrence occurred during a median contrast-enhanced CT follow-up of 6 months. Conclusions Our results suggest that vertebroplasty, using Spinejack implantation for the treatment and stabilization of painful vertebral compression fractures, secondary to Multiple Myeloma is a safe and effective procedure with long - term pain relief and restoration of vertebral height.